Griscelli syndrome with malnutrition: a diagnostic challenge - Singh, Jyoti; Adil, Mohammad; Amin, Syed Suhail; Tuz Zahra, Fatima (Dermatology Review/Przegląd Dermatologiczny, 2022)
Griscelli syndrome is a rare autosomal recessive disorder characterized by hypopigmentation of skin and hair. Griscelli syndrome type 2, one of the three subtypes of Griscelli syndrome, is characterized by recurrent infections, in addition to pigmentary abnormalities. We present the case of a 15-year-old girl with late onset of Griscelli syndrome type 2 features: pigmentary changes of hair and skin, hepatosplenomegaly, pancreatitis and pancytopenia. We also highlight the diagnostic dilemma in patients with coexisting features of malnutrition. Both conditions show some overlapping clinical features and hence, establishing a diagnosis may be challenging.